SALTS OF ALIPHATIC CARBOXYLIC ACIDS: RAMAN SPECTRA AND ION PAIRING IN HYDROTHERMAL SOLUTIONS CONTAINING SODIUM AND CALCIUM ACETATES - Frantz J.D. (My University, 2000)
A 2.0 molal solution of sodium acetate and 0.1, 0.5, and 1.0 molal solutions of calcium acetate were investigated by Raman spectroscopy from 22 to 400°C at 1000 and 2000 bar. Experiments were performed in a special hydrothermal pressure vessel fitted with conical diamond windows. In the case of the sodium acetate solution, perturbations of the internal vibrational modes of the acetate ligand resulting from the formation of sodium acetate ion pairs were undetectable. In the case of calcium acetate, however, the OCO bending mode, the C-C symmetric stretching mode, and the C-O symmetric stretching mode all showed evidence of ion pairing between calcium and acetate. The degree of formation of the ion pairs increased with increasing temperature, increasing concentration, and decreasing pressure. Mass action constants were calculated for the reaction involving Ca2+, CH3COO-, and CaCH3COO+ which compare favorably with theoretically derived constants and with values derived from solubility experiments. The solutions existed metastably until temperatures approaching 480°C at which the acetate ligands underwent decarboxylation resulting in the formation of bicarbonate and methane. Combining mass action constants derived from this study with constants derived from the literature, distributions of the aqueous species were computed for the experimental conditions of the spectral measurements.
Keywords: RAMAN SPECTROSCOPY; ACETATE; HYDROTHERMAL